Greenhouse Gas Emissions Non-Cattle Confinement Buildings: Monitoring, Emission Factors and Mitigation - Godbout, S.; Pelletier, F.; Larouche, J.P.; Belzile, M.; Feddes, J.J.R.; Fournel, S.; Lemay, S.P.; Palacios, J.H. (IntechOpen, 2012)
None